Da lepra à hanseníase : políticas de combate à hanseníase em Manaus (1940-1980) - Cabral, Adriana Brito Barata (2023)
This research analised diseases fighting policies at Manaus effected from 1940, where were built the new Leper colony, Antônio Aleixo colony, the Gustavo Capanema preventorium, both inaugurated in 1942 and Alfredo da Matta dispensarium inaugurated at 1955. The three togheter were the principal tools to fight the disease at the state of Amazonas, followed by the guidelines from the Federal Government, started at Varga’s governement by his Public Health and Education Minister Gustavo Capanema. This model was recommended since 1935, and lasted till it deactivation in the mid of 1980. Particularly here at Manaus the deactivation policies of that institutional apparatus formed by Leper Colony, dispensarium and preventorium was deactivated in 1978, extending over the followed years, the Antônio Aleixo Hospital-Colony was transformed into a neighborhood from the East zone of The Manaus City. The Gustavo Capanema educandarium, shelter to healthy children from the sicks, was also deactivated in 1978. Only the Alfredo da Matta dispensarium stills active in Manaus, the State Institution linked to the Health that still works at the disease control in our city, just changed the name today, becoming the Alfredo da Matta Hospital Foundation of Demartology and Venearology. With the deactivation policies, the transformation from Hospital-Colony to neighborhood was a process that started in 1978 enduring to the 1980- 1990 decades, seen to have been a long process that ended up in the born of Reintegration Moviment for People Affected by Leprosy (MORHAN), organ that fights for better life conditions to the former interns and habitants of today’s Antônio Aleixo colony